Ribonuclease 4 protects neuron degeneration by promoting angiogenesis, neurogenesis, and neuronal survival under stress - Li, Shuping; Sheng, Jinghao; Hu, Jamie K.; Yu, Wenhao; Kishikawa, Hiroko; Hu, Miaofen G.; Shima, Kaori; Wu, David; Xu, Zhengping; Xin, Winnie; Sims, Katherine B.; Landers, John E.; et al. (Angiogenesis (London), 2013)
Altered RNA processing is an underlying mechanism of amyotrophic lateral sclerosis (ALS). Missense mutations in a number of genes involved in RNA function and metabolisms are associated with ALS. Among these genes is angiogenin ( ANG ), the fifth member of the vertebrate-specific, secreted ribonuclease superfamily. ANG is an angiogenic ribonuclease, and both its angiogenic and ribonucleolytic activities are important for motor neuron health. Ribonuclease 4 ( RNASE4 ), the fourth member of this superfamily, shares the same promoters with ANG and is co-expressed with ANG . However, the biological role of RNASE4 is unknown. To determine whether RNASE4 is involved in ALS pathogenesis, we sequenced the coding region of RNASE4 in ALS and control subjects and characterized the angiogenic, neurogenic, and neuroprotective activities of RNASE4 protein. We identified an allelic association of SNP rs3748338 with ALS and demonstrated that RNASE4 protein is able to induce angiogenesis in in vitro, ex vivo, and in vivo assays. RNASE4 also induces neural differentiation of P19 mouse embryonal carcinoma cells and mouse embryonic stem cells. Moreover, RNASE4 not only stimulates the formation of neurofilaments from mouse embryonic cortical neurons, but also protects hypothermia-induced degeneration. Importantly, systemic treatment with RNASE4 protein slowed weight loss and enhanced neuromuscular function of SOD1 G93A mice.